Identification of Suitable Sites for Water Harvesting Structures in Kecheri River Basin. (2016) - Abdulla Umar Naseef, T.; Thomas, Reeba
Abstract: Water is the most precious resource on the earth which is essential for the existence of life. Though Kerala is blessed with two prominent monsoons with an average rainfall of around 3000 mm, it experiences water scarcity in off monsoon seasons. Peculiarities such as steep slope and undulating terrain accelerate surface flow and hence most of the water received as rainfall goes as unutilized. Water Harvesting is the best technique which can be used effectively to trap the unutilized surface runoff and thereby increase the groundwater recharge. But these structures have to be located at places where water is available in excess and conditions are favourable for enhanced infiltration. The objective of this study is to identify suitable sites for water harvesting structures. For ideally locating the sites, the guidelines put forward by NRSA, Hyderabad for Integrated Mission for Sustainable Development (IMSD), is being followed. ArcGIS is used for the spatial analysis and the sites are located by overlaying thematic maps of land use, soil, slope, runoff potential, soil permeability and stream order. It is found that 37 percentage of the total area is ideal for constructing check dam, 7 percentage for farm pond, 4 percentage for percolation pond and about 2 percentage for subsurface dyke. Check dams are the most suited one and location for subsurface dykes is sparse. Locations of water harvesting structures are suggested by conducting meteorological and topographical analysis. However, for the practical implementation of these structures, viability of other considerations such as economy, social implications, practical feasibility etc. need to be considered.